A Qualitative Study Of Pedagogical Issues Arising From The Introduction Of The Malaysian – Smart School Initiative - Cloke, Chris; Sharif , Sabariah; Ambotang, Abdul Said (Penerbit Universiti Sains Malaysia, 2006)
The Malaysia Smart School initiative began in 1999. The intention was to equip Malaysian schools with an impressive array of information technology (IT) facilities and to bring about associated innovation in teaching and learning as well as to equip Malaysian children with the necessary skills to be effective in a modern society. It was initially beset with difficulties arising from the economic situation in Malaysia. Our research focused on the pedagogical changes which teachers had to bring about and how to enacted them. Our approach was to analyse the work of 17 teachers using a qualitative software tool using a literature-based framework of analysis. It was clear from the sample of lessons studied in-depth, that remained constraints on the teacher. There were no accompanying curriculum changes which meant that teachers needed to understand the key purpose of the innovation and should be given the necessary support to enable it to happen.